Automated quality control for the haematology laboratory. Issue 9 (September 1974) - Cavill, I.; Ricketts, C.
Abstract : Two simple methods of using sophisticated statistical techniques to analyse intralaboratory quality control data are described. One method uses a plastic grid to assess the cumulative sum (cusum) graph. An equivalent procedure, which may be carried out by a laboratory computer, gives automated on-line quality control of the Coulter S blood counter. The possible development of simple apparatus to carry out the same function is discussed.